Multi-wavelength ytterbium doped fiber laser based on longitudinal mode interference - Shahabuddin, Nurul Shahrizan; Ismail, Mohd Afiq; Paul, Mukul Chandra; Damanhuri, Siti Sarah Ahmad; Harun, Sulaiman Wadi; Ahmad, Harith; Pal, Mrinmay; Bhadra, Shyamal Kumar (IOP Publishing, 2012)
Multi-wavelength Ytterbium-doped fiber laser (YDFL) is demonstrated using a longitudinal mode interference assisted by a four-wave mixing (FWM) effect in a ring laser cavity. The gain medium is a 16 m long of the fabricated (Ytterbium-doped fiber) YDF, which has a core composition of 0.8 wt % of Yb 2O 3, 1.8 wt % of Al 2O 3 and 23 wt % of GeO 2, Ytterbium ion fluorescence lifetime of 1.1 ms and absorption of 9.0 dB/m at the pump wavelength of 976 nm. 20 m long photonic crystal fiber (PCF) is used to provide FWM effect so that the energy of different oscillating lines can be redistributed to improve multi-wavelength operation. The proposed laser generates 12 lines of optical comb with a line spacing of approximately 0.59 nm at 1035 nm region.